If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7c + 9 = c + 1 Reorder the terms: 9 + 7c = c + 1 Reorder the terms: 9 + 7c = 1 + c Solving 9 + 7c = 1 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. 9 + 7c + -1c = 1 + c + -1c Combine like terms: 7c + -1c = 6c 9 + 6c = 1 + c + -1c Combine like terms: c + -1c = 0 9 + 6c = 1 + 0 9 + 6c = 1 Add '-9' to each side of the equation. 9 + -9 + 6c = 1 + -9 Combine like terms: 9 + -9 = 0 0 + 6c = 1 + -9 6c = 1 + -9 Combine like terms: 1 + -9 = -8 6c = -8 Divide each side by '6'. c = -1.333333333 Simplifying c = -1.333333333
| lnx+ln(x+3)=1 | | 6sec^2(x)-8=0 | | 9-2x-6=8x+4-17x | | ln(x+1)-ln(x-2)=inx | | 4w^2+6w+1=0 | | 5y+2y=-42 | | 8x^2+15x-2=0 | | 3x-.04x=-20.03 | | 8x=84-6x | | 7k^2-9k-10= | | 7z^2-48z-834=0 | | 39-4z=4 | | 155=6(x)-3+4(x) | | 30(4x-7)-88x=-7(11-5x)-3x-133 | | -14+12= | | 2y^2-15y-297=0 | | 27-4x=11 | | 6(4x-5)=2x-2(11-6x) | | 5x+5=-4-10x | | 102-4x=4x+16 | | -10x-4=5-9x | | (4+7)x=9x | | 10x-4x+8=6x+7 | | 6x+2=10-2x | | x+(x+4)+(2x+4)=180 | | 3+9x=99 | | 2-y=28 | | y^2-9y+81=0 | | 2y^2-12y+10=0 | | 3x+9x+2=8+18 | | 8x+22=2x+148 | | 102=2(6+2x)+2(x) |